Fatigue and neuropsychiatric symptoms in Parkinson’s disease: a narrative review - Bojtos, Lidia; Rodríguez-Antigüedad, Jon; Pagonabarraga, Javier; Martínez-Horta, Saül; Kulisevsky, Jaime (Frontiers in Neurology, 2025)
Fatigue in Parkinson’s disease (PD) is a highly prevalent and disabling non-motor symptom, often manifesting early and worsening over the disease course. Despite its significant impact on quality of life, fatigue remains underrecognized and poorly managed in clinical practice. It is a complex, multidimensional syndrome encompassing cognitive, emotional, and physical components. Its pathophysiology is multifactorial, involving disrupted dopaminergic, serotonergic, and glutamatergic signaling across fronto-striatal and limbic circuits. Fatigue frequently overlaps with neuropsychiatric symptoms such as apathy, depression, anxiety, and cognitive impairment, complicating both diagnosis and treatment. Although these conditions are clinically distinct, they share overlapping neural substrates and may influence each other’s presentation and severity. Currently available therapeutic options for PD-related fatigue are limited, with rasagiline considered only “possibly useful,” and most other pharmacologic and non-pharmacological strategies lacking rigorous evidence. This narrative review is based on a non-systematic PubMed literature search of peer-reviewed articles in English up to April 2025, with additional relevant studies identified through reference lists. It examines the clinical and neurobiological intersections between fatigue and neuropsychiatric symptoms in PD, highlighting key diagnostic challenges, treatment limitations, and future directions. Standardizing terminology, dissecting fatigue from overlapping neuropsychiatric symptoms, identifying reliable biomarkers, and conducting well-designed, mechanism-based clinical trials are essential next steps to redefine fatigue as a measurable and treatable symptom in PD.